Challenging Treatment of Drug-Resistant Tuberculosis during Pregnancy: A Case Report - Ni Luh Putu Eka Arisanti; Ni Putu Ayu Widiasari; Ni Wayan Candrawati; Ida Ayu Jasminarti Dwi Kusumawardani; Ida Bagus Ngurah Rai; Made Ary Sarasmita (Faculty of Medicine Universitas Airlangga, 2022)
Introduction: Globally, drug-resistant tuberculosis (TB) still has a high number of cases. Pregnant women are one of the high-risk populations for TB infection, especially multidrug resistance (MDR)/Rifampicin resistance (RR) TB. Physiological differences in pregnant women and the safety of the fetus make drug resistance TB treatment challenging. Case: A 20-year-old woman was 22 weeks pregnant while undergoing the third month of the late phase for short-regimen. Thus, Kanamycin was one of her early phase treatment combinations during the first trimester of pregnancy. After we consulted with other departments, especially the obstetric department, we decided not to change her regimen. Her chief complaint before treatment was cough with white sputum and fluctuated shortness of breath for two months. The patient only experienced minor side effects in the early treatment phase. The patient was cured of MDR TB on 8 October 2020 at 34 weeks of gestation. Her baby was born on 10 November 2020 at 37 weeks without congenital abnormality. Observation for her baby continued by the pediatric department. The last follow-up of her baby in the middle of 2022 found no abnormality in the child’s growth and development. Conclusion: Drug-resistant TB therapy in pregnant women requires the collaboration of a multidisciplinary team to consider the benefits and risks of the therapy based on gestational age and disease severity.